A Developing Model Of Relationship Among Service Quality, Consumer Satisfaction, Loyalty and Word of Mouth In Islamic Banking - S. Suryani; Hendryadi Hendryadi (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
This research aims to develop a measurement tool of service quality in Islamic banking sector, and examine its relationship among satisfaction, word of mouth (WOM), and consumer loyalty. A convenience sampling of 235 respondents collected from seven locations in the Lhokseumawe, Aceh. Partial least square -structural equation modeling- (PLS-SEM) was used to test the research hypotheses. The results revealed that the quality of service has four dimensions, they are: service portfolio and assurance/SPA, tangibles/TAN, reliability of communication/COM, and Islamic values/IVA. The PLS-SEM results suggest that SPA and COM are dominant factors affecting satisfaction, and satisfaction were significantly related to WOM and loyalty. Loyalty also positively and significantly related to WOM.DOI:10.15408/aiq.v7i1.1357